Rabbit Food Pellet Formulation from Sustainable Resources - Jamaluddin, Nurul Syasya; Mohd Razman, Nayli Qaisara Fatini; Abdul Halim, Norhazimah (Multidisciplinary Applied Research and Innovation, 2023)
Food pellets are the best substitute for grass to provide complete nutrition for rabbits [1]. As time goes by, rabbit food pellets are progressively getting more expensive and affect the breeders whom they can no longer afford to raise rabbits. A sustainable resource such as Mucuna bracteata is planted abundantly in inter rows of rubber and oil palm in Malaysia. The goal of this research is to create a new formulation of rabbit food pellets using Mucuna bracteata. The quality of the pellet will be tested according to its pellet durability and appearance. The pellet durability test will be carried out using a coating pan. The ingredients to produce the new formulations are soybean meal, rice bran, wheat pollard, palm kernel cake, and DIY-Rabbit and Mucuna bracteata. There are three formulations where each contains a different amount of Mucuna bracteata. Mucuna bracteata was used to substitute wheat pollard in the pellet formulation. Each feed mix is 2 kg and is inserted into the machine to produce a feed pellet. The pellet was cooled and dried after the pelleting process. For color evaluation, the pellets get darker with the increment of Mucuna bracteata content. As for the size of the pellet, all three formulations have the same diameter which is 4mm. It was observed that the pellet durability index increases with increasing Mucuna bracteata content in the formulation. Further research can be done to investigate the effect of Mucuna bracteata in food pellets on rabbit growth.